From the tragedy to the success of the commons: international trade as the articulating axis of sustainable economic development - Hernández Zuluaga, María Andrea (2026)
This article questions the viability of the current international economic order based on the availability of finite natural resources, with a special focus on its limited scope to respond to the environmental needs and expectations of this era. According to the theory of the Tragedy of the Commons, humans act selfishly in the management of natural resources, leading to their overexploitation and depletion. In contrast, Ostrom shows that communities are capable of managing common resources efficiently and sustainably. This article analyzes the way in which various actors in international trade are working towards a system of sustainable economic development for present and future generations, animals, and the planet. The purpose of this article is to demonstrate that, through international trade, it is possible to transition from the Tragedy to the Success of the Commons.